Pengaruh Freight Forwarder Dan Kualitas Layanan Terhadap Efektivitas Proses Ekspor Import Pada PT DAEHAN GLOBAL LOGISTICS - Fenny Sandora; Achsanul Nashir (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.In the structure of international trade, exports also reflect a country’s competitiveness. The higher thevalue and diversity of exports, the stronger a country’s position in the global supply chain. Therefore,maintaining stability and growth in exports is a strategic priority that involves not only producers butalso the entire supporting system including logistics, transportation, and trade policies. This researchaimed to determine the extent of the influence between the performance of freight forwarders andservice quality on the effectiveness of the export process at PT Daehan Global Logistic. This researchused a quantitative method with 50 respondents, and used linear regression analysis as the dataanalysis technique. The results of this research showed that partially, the variable of Freight ForwarderPerformance had no significant influence on the Effectiveness of the Export Process, with a significancevalue of 0.093. Meanwhile, the Service Quality variable had a positive and significant influence on theEffectiveness of the Export Process with a significance value of 0.000. Simultaneously, both variableshad a significant influence on the Effectiveness of the Export Process, with a significance value of0.000 and an adjusted coefficient of determination (Adjusted R²) of 0.526. This meant that 52.6% ofthe variation in the Effectiveness of the Export Process could be explained by the variables of FreightForwarder Performance and Service Quality, while the remaining 47.4% was influenced by other factorsnot examined in this research.Keywords: Freight Forwarder Performance, Service Quality, Effectiveness of The ExportProcess, International Trade